Journal of NeuroEngineering and Rehabilitation - Reinkensmeyer, David J.
Journal of NeuroEngineering and Rehabilitation considers manuscripts on all aspects of research that result from cross-fertilization of the fields of neuroscience, biomedical engineering, and physical medicine and rehabilitation. JNER provides a forum for researchers and clinicians interested in understanding the way neuroscience and biomedical engineering are continuing to reshape physical medicine and rehabilitation. JNER hosts the introduction of new methods and the discussion of their clinical implications, and offers an opportunity to publish, in a timely manner, articles relevant to the intersection of these three fields.